The clinical application of laparoscope‐assisted peritoneal vaginoplasty for the treatment of congenital absence of vagina. Issue 3 (2nd March 2016) - Qin, Chenglu; Luo, Guangnan; Du, Min; Liao, Shi; Wang, Chunping; Xu, Keke; Tang, Jie; Li, Baoyan; Zhang, Juanjuan; Pan, Hongxin; Ball, Tyler W.; Fang, Yujiang
Abstract: Objective: To evaluate the outcomes of laparoscope‐assisted peritoneal vaginoplasty for the treatment of congenital vaginal atresia. Methods: A retrospective study enrolled patients diagnosed with congenital vaginal atresia who were treated with one of two different laparoscope‐assisted peritoneal vaginoplasty techniques (named Luohu‐one and Luohu‐two) between October 31, 2001 and December 31, 2014. Operative time, intraoperative bleeding volume, surgical difficulty, complications, and post‐procedure sexual satisfaction were reported. Results: Data were collected for 620 patients. The Luohu‐one procedure was used in the treatment of 145 patients, while 475 patients were treated with the Luohu‐two procedure. In 5 (0.8%) patients, it was necessary to perform a sigmoid colon vaginoplasty. During surgery, 16 patients experienced a rectal injury, among whom, 9 patients experienced a rectal–vaginal fistula. Follow‐up data extending to 7 years were available for 285 patients. Of these 285 patients, 231 agreed to report details of their sexual experiences. In total, 222 (96.1%) patients reported being very satisfied with their vaginal conditions and sex life. The Luohu‐two procedure demonstrated shorter operative and recovery time, and reduced intraoperative bleeding. However, both procedures demonstrated satisfactory results. Conclusion: Laparoscope‐assisted peritoneal vaginoplasty demonstrated good safety and effectiveness in the treatment of patients with congenital vaginal atresia.